Long‐term changes in bat activity in Quebec suggest climatic responses and summer niche partitioning associated with white‐nose syndrome. Issue 12 (2nd June 2020) - Faure‐Lacroix, Julie; Desrochers, André; Imbeau, Louis; Simard, Anouk
Abstract: In North America, the greatest and most sudden threat to hibernating bats is white‐nose syndrome (WNS), which has caused massive declines in populations since 2006. Other determinants of bat dynamics, such as the climate, and the effect of reduction in the number of individuals sharing foraging space and summer roosting habitat may have an effect on population dynamics. We analyzed transect acoustic bat surveys conducted with ultrasonic detectors in 16 regions in Quebec, Canada, between 2000 and 2015. We used piecewise regression to describe changes in activity over time for each species and a meta‐analytic approach to measure its association with the North Atlantic Oscillation (NAO). As expected, mouse‐eared bat ( Myotis spp.) activity sharply declined after the onset of WNS, down by 79% after 3 years. In contrast, big brown/silver‐haired bat activity increased over the same period, possibly due to a release of competition. Hoary bats and red bats remained present, although their activity did not increase. Myotis activity was positively correlated with a one‐year lag to the NAO index, associated with cold conditions in winter, but warm autumns. Big brown/silver‐haired and hoary bats were also more active during NAO‐positive years but without a lag. We conclude that combinations of threats may create rapid shifts in community compositions and that a more balanced research agenda that integrates a wider range of threats would help better understand and manage those changes. Abstract : We analyzed 10 years of acoustic bat monitoring data from 16 regions in the province of Quebec, Canada, before and after the onset of white‐nose syndrome (WNS). We found a general response to climate for some species, a sharp decline in activity for the species affected by WNS, and subsequently an apparent relaxation of niche partitioning between large, high‐flying species and small, low‐flying species.